Circular RNAs: Their Role in the Pathogenesis and Orchestration of Breast Cancer - He, Xiao; Xu, Tao; Hu, Weijie; Tan, Yufang; Wang, Dawei; Wang, Yichen; Zhao, Chongru; Yi, Yi; Xiong, Mingchen; Lv, Wenchang; Wu, Min; Li, Xingrui; et al. (Frontiers in Cell and Developmental Biology, 2021)
As one of the most frequently occurring malignancies in women, breast cancer (BC) is still an enormous threat to women all over the world. The high mortality rates in BC patients are associated with BC recurrence, metastatic progression to distant organs, and therapeutic resistance. Circular RNAs (circRNAs), belong to the non-coding RNAs (ncRNAs), are connected end-to-end to form covalently closed single-chain circular molecules. CircRNAs are widely found in different species and a variety of human cells, with the features of diversity, evolutionary conservation, stability, and specificity. CircRNAs are emerging important participators in multiple diseases, including cardiovascular disease, inflammation, and cancer. Recent studies have shown that circRNAs are involved in BC progress by regulating gene expression at the transcriptional or post-transcriptional level via binding to miRNAs then inhibiting their function, suggesting that circRNAs may be potential targets for early diagnosis, treatment, and prognosis of BC. Herein, in this article, we have reviewed and summarized the current studies about the biogenesis, features, and functions of circRNAs. More importantly, we emphatically elucidate the pivotal functions and mechanisms of circRNAs in BC growth, metastasis, diagnosis, and drug resistance. Deciphering the complex networks, especially the circRNA-miRNA-target gene axis, will endow huge potentials in developing therapeutic strategies for combating BC.